The woman in battle : a narrative of the exploits, adventures, and travels of Madame Loreta Janeta Velazquez, otherwise known as Lieutenant Harry T. Bufford, Confederate States Army - Velazquez, Loreta Janeta, 1842-1923.; Worthington, C. J. (Chapel Hill : University of North Carolina at Chapel Hill Library, 2017)
Loreta Janeta Velazquez was the daughter of a Spanish official living in Cuba. As a young girl she was sent to school in New Orleans, where she ran away and married a U.S. Army officer. After the outbreak of the war, she persuaded her husband to renounce his commission and to join the Confederate forces. After he was killed in battle, Velazquez disguised herself as a man so that she could serve, eventually doing so as an officer, a spy, and a blockade runner. The Woman in Battle tells the amazing story of Velazquez's experiences in a male-dominated world, offering a unique perspective on life as a soldier and detailing her many adventures, including fighting in the First Battle of Bull Run and Shiloh, where she was allegedly wounded. Upon the book's publication in 1876, its veracity was questioned, and it continues to be debated by contemporary historians to this day.
CHAPTER XXXVIII. IN THE INDIANAPOLIS ARSENAL.-FAILURE OF THE PROJECTED RAID. CHAPTER XXXIX. BLOCKADE-RUNNING.; CHAPTER XL. AN ATTACK ON THE FEDERAL TREASURY.; CHAPTER XLI. COUNTERFEITING AND BOGUS BOND SPECULATIONS.; CHAPTER XLII. BOUNTY-JUMPING.; CHAPTER XLIII. THE SURRENDER OF LEE.; CHAPTER XLIV. THE ASSASSINATION OF PRESIDENT LINCOLN, AND END OF THE WAR.; CHAPTER XLV. A TOUR THROUGH EUROPE.; CHAPTER XLVI. SOUTH AMERICAN EXPEDITION.; CHAPTER XLVII. VENEZUELA.; CHAPTER XLVIII. DEMERARA, TRINIDAD, BARBADOES, AND ST. LUCIA; CHAPTER XLIX. ST. THOMAS AND CUBA.; CHAPTER L. ACROSS THE CONTINENT.
Print version record.
CHAPTER LI. MINING IN UTAH AND NEVADA.-THE MORMONS AND THEIR COUNTRY. CHAPTER LII. COLORADO, NEW MEXICO, AND TEXAS.-CONCLUSION.
eBooks on EBSCOhost
Keywords: Velazquez, Loreta Janeta, -- 1842-1923.; Velazquez, Loreta Janeta, -- 1842-1923.; Velazquez, Loreta Janeta, -- 1842-1923; United States -- History -- Civil War, 1861-1865 -- Personal narratives, Confederate; Women soldiers -- Confederate States of America -- Biography; Women spies -- Confederate States of America -- Biography; Cubans -- Confederate States of America -- Biography; United States -- History -- Civil War, 1861-1865 -- Participation, Female; United States -- History -- Civil War, 1861-1865 -- Participation, Cuban; États-Unis -- Histoire -- 1861-1865 (Guerre de Sécession) -- Récits personnels des confédérés.; Femmes militaires -- États confédérés d'Amérique -- Biographies; Espionnes -- États confédérés d'Amérique -- Biographies; Cubains -- États confédérés d'Amérique -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- United States -- State & Local -- General; HISTORY -- United States -- Civil War Period (1850-1877); Cubans; Military participation -- Cuban; Military participation -- Female; Women soldiers; Women spies; United States; United States -- Confederate States of America; 1861-1865; Biographies; History; Personal narratives -- Confederate